Water-sensitive urban design: sponge-cities and “smart” landscapes - E. Yu. Zaykova; S. S. Feofanova (Vestnik MGSU)
Introduction. In 2023, an increase in cases of urban flooding was recorded worldwide. The amount of stormwater has increased manifold, but there is nowhere to apply this supernumerary resource in the cities. Water-sensitive design of territories should become a priority in the planning of cities and updating of normative documents of the urban sphere in the face of global warming.Materials and methods. The given analysis of climatic data of the study area is of key importance in calculating the irrigation rate for the functioning of green infrastructure in urban conditions. It is proposed to consider vegetative irrigation — the most important and regulated watering activity, which is vital for all plants in urban conditions.Results. Stormwater management will reduce irrigation costs and simplify the maintenance of urban green spaces throughout growing season. The amendments and additions proposed by the authors of the regulatory documents of the Russian Federation in the field of green infrastructure will facilitate the implementation of a new ecosystem approach in practice. The light conditions for the high-quality functioning of the green infrastructure in the study area are also considered.Conclusions. The author’s biotopes are sustainable by technological solutions of engineering preparation of the territory, developed in the context of the spirit of the place using plants of local flora based on the developed regulatory recommendations for the new concept of water-sensitive design of the urban environment.